Age Bar for the Retirement of Politicians - Neupane, Alaka; Ghimire, Maya Nath (Nepal Journal of Multidisciplinary Research, 2023)
Representation of people are expected to be reliable. To maintain the reliability, there needs certain limitation regarding the age. This paper discusses the reasons why there needs to be age bar for the retirement of politicians. Moreover, it illustrates the grounds that helps in flourishment of country upon having such limitations. Not only the flourishment of a country, it helps in giving the space for the ideas and strength of younger generation.